1989
DOI: 10.1007/bf00004728
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 and the renal handling of phosphate in American eels

Abstract: Cholecalciferol (Vitamin D3) increased plasma inorganic phosphate concentration in American eels,Anguilla rostrata, in a dose-dependent fashion. This response was more marked in phosphate loaded fish. In control as well as phosphate loaded eels the hyperphosphatemic response to D3 was associated with a sharp reduction in renal phosphate clearance relative to(14)C-polyethelene glycol (PEG) clearance. Glomerular filtration and urine flow rates were not affected by D3. As renal phosphate clearance, even in phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…2000; Sugiura et al . 2000a; and the study described here), it can be concluded that regulation of renal phosphate excretion contributes to the maintenance of P homeostasis in salmonids, as has been demonstrated in eels (Fenwick & Vermette 1989).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…2000; Sugiura et al . 2000a; and the study described here), it can be concluded that regulation of renal phosphate excretion contributes to the maintenance of P homeostasis in salmonids, as has been demonstrated in eels (Fenwick & Vermette 1989).…”
Section: Resultssupporting
confidence: 73%
“…According to the results of Rodehutscord et al (2000) and Sugiura et al (2000a), below a threshold level of dietary P (considered to be the P requirement), dissolved waste P is fairly constant, but above this threshold, dissolved waste P increases with dietary P level. Based on these studies (Bureau & Cho 1999;Rodehutscord et al 2000;Sugiura et al 2000a; and the study described here), it can be concluded that regulation of renal phosphate excretion contributes to the maintenance of P homeostasis in salmonids, as has been demonstrated in eels (Fenwick & Vermette 1989).…”
Section: Dietsupporting
confidence: 56%
“…However, the effects of different dietary vitamin D 3 levels on phosphorus absorption or deposition have been controversial. In the previous researches, vitamin D 3 elevated serum phosphorus in American eels, Anguilla rostrata (Fenwick and Vermette 1989), carp, Cyprinus carpio (Swarup et al 1991), and rainbow trout, Oncorhynchus mykiss (Avila et al 1999), elevated phosphorus concentrations in the skin of trout, Salmo gairdneri (Hilton and Ferguson 2006), and in channel catfish, Ictalurus punctatus (Lovell and Li 1978). Coloso et al (2001) also suggested that vitamin D 3 could improve phosphorus deposit efficiency in low phosphorus diets in rainbow trout.…”
Section: Effects Of Dietary Vitamin D 3 On Body Compositionmentioning
confidence: 94%
“…1984) and freshwater mud eel A. cuchia (Srivastav 1983) plasma phosphate increased after IP vitamin D 3 injection. Apparently, in addition to phosphate reabsorption in the kidney (Fenwick & Vermette 1989), it can be mobilized by vitamin D 3 metabolites from a nondietary source, presumably bone or soft tissues (Lopez et al . 1977).…”
Section: Actions Of Vitamin D3 Metabolitesmentioning
confidence: 99%